The New Genetic Evidence on Same-Gender Sexuality: Implications for Sexual Fluidity and Multiple Forms of Sexual Diversity. Issue 7 (2nd September 2021) - Diamond, Lisa M.
ABSTRACT: In September of 2019, the largest-ever (N = 477, 522) genome-wide-association study of same-gender sexuality was published in Science . The primary finding was that multiple genes are significantly associated with ever engaging in same-gender sexual behavior, accounting for between 8–25% of variance in this outcome. Yet an additional finding of this study, which received less attention, has more potential to transform our current understanding of same-gender sexuality: Specifically, the genes associated with ever engaging in same-gender sexual behavior differed from the genes associated with one's relative proportion of same-gender to other-gender behavior. I review recent research on sexual orientation and sexual fluidity to illustrate how these findings speak to longstanding questions regarding distinctions among subtypes of same-gender sexuality (such as mostly-heterosexuality, bisexuality, and exclusive same-gender experience). I conclude by outlining directions for future research on the multiple causes and correlates of same-gender expression.